Integrating Islamic values into waste management: Efforts to raise environmental awareness from an early age through guidance on memorizing short hadiths at MDTA Al-Falah, Hamlet 2, Neglasari Village - Nunung Nursyaidah; Tajul Muttaqin; Dyah Wulandari (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Waste management is an increasingly urgent problem amidst public awareness of the importance of cleanliness and environmental sustainability. One approach that can be implemented to overcome this problem is to integrate Islamic values in education from an early age, especially through teaching that involves memorizing short hadiths. This research aims to explore the application of Islamic values in waste management in educational environments, especially at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Falah Dusun 2, Neglasari Village. The approach used is qualitative with observation and interview techniques with teachers, parents and students at MDTA Al-Falah. Through a program to memorize short hadiths related to cleanliness, such as the hadith which states "Cleanliness is part of faith," children at MDTA are taught to interpret and apply the principles of cleanliness in their daily lives. This research found that assistance in memorizing hadiths can shape the character of children who care about cleanliness and the surrounding environment, as well as increase their awareness of managing waste responsibly. Apart from that, the integration of Islamic values in teaching at MDTA Al-Falah also plays a role in building a sustainable environmentally conscious culture. Through this approach, it is hoped that the younger generation can become agents of change who are able to create a cleaner and healthier environment in the future. The conclusion of this research shows that the integration of Islamic values in waste management can be an effective effort to instill environmental awareness in children from an early age.